Continuous renal replacement therapy in elderly with acute kidney injury - Medina-Liabres, Kristianne Rachel P. (Korean J Intern Med, 2020)
The objective of this article is to raise awareness among physicians of the increasing incidence of acute kidney injury in the elderly population and the utility of continuous renal replacement therapy (CRRT) in its management. While CRRT is frequently applied in younger patients, its use in elderly patients is less frequent, for various reasons, including resistance to such an aggressive intervention from the family and the healthcare team. However, predictors of prognosis have been identified and some studies have concluded that advanced age is not associated with poor outcomes. Decisions regarding management are more complex when dealing with the elderly but like very other patient, the approach should be patient-centered.